Minor impact of probiotic bacteria and egg white on Tenebrio molitor growth, microbial composition, and pathogen infection - Savio, Carlotta; Herren, Pascal; Rejasse, Agnès; Rios, Alfredo; Bourelle, William; Bruun-Jensen, Annette; Lecocq, Antoine; van Loon, Joop J. A.; Nielsen-LeRoux, Christina (Frontiers in Insect Science, 2024)
The industrial rearing of the yellow mealworm (Tenebrio molitor) for feed and food purposes on agricultural by-products may expose larvae and adults to entomopathogens used as biocontrol agents in crop production. Bacterial spores/toxins or fungal conidia from species such as Bacillus thuringiensis or Metarhizium brunneum could affect the survival and growth of insects. Therefore, the aim of this study was to investigate the potential benefits of a wheat bran diet supplemented with probiotic bacteria and dried egg white on larval development and survival and its effects on the gut microbiome composition. Two probiotic bacterial species, Pediococcus pentosaceus KVL B19-01 and Lactiplantibacillus plantarum WJB, were added to wheat bran feed with and without dried egg white, as an additional protein source, directly from neonate larval hatching until reaching a body mass of 20 mg. Subsequently, larvae from the various diets were exposed for 72 h to B. thuringiensis, M. brunneum, or their combination. Larval survival and growth were recorded for 14 days, and the bacterial microbiota composition was analyzed using 16S rDNA sequencing prior to pathogen exposure and on days 3 and 11 after inoculation with the pathogens. The results showed increased survival for T. molitor larvae reared on feed supplemented with P. pentosaceus in the case of co-infection. Larval growth was also impacted in the co-infection treatment. No significant impact of egg white or of P. pentosaceus on larval growth was recorded, while the addition of Lb. plantarum resulted in a minor increase in individual mass gain compared with infected larvae without the latter probiotic. On day 14, B. thuringiensis was no longer detected and the overall bacterial community composition of the larvae was similar in all treatments. On the other hand, the relative operational taxonomic unit (OTU) abundance was dependent on day, diet, and probiotic. Interestingly, P. pentosaceus was present throughout the experiments, while Lb. plantarum was not found at a detectable level, although its transient presence slightly improved larval performance. Overall, this study confirms the potential benefits of some probiotics during the development of T. molitor while underlining the complexity of the relationship between the host and its microbiome.